(untitled) (Pengelolaan Sumberdaya Pembangunan, 2021)
The increase in the number of incoming citizens in Indonesia is caused by several factors such as tourism, business and professional workers. With this development, Indonesia has a great potential for disturbances in terms of theory, cross-border violations, criminal offenses and other crimes that have the potential to disrupt the integrity of the Republic of Indonesia. North Sulawesi is one of the regions where the growth in visits by foreign nationals has increased every year before the Covid 19 pandemic. This development is partly due to the visa-free policy for several countries, with many foreign citizens who also have violations both in administrative and criminal terms. Therefore, supervision of foreigners is very necessary. The supervision of foreigners is carried out in a coordinating pattern of institutions / agencies in the regions. This is in accordance with the mandate of Article 69 paragraph (1) of Law Number 6 of 2011 concerning Immigration states that to carry out immigration control of the activities of foreigners in the Indonesian Territory, the Minister forms a foreigner supervision team (Tim PORA) whose members consist of agencies or related government agencies, both at the central and regional levels. Keywords: Policy, Supervision, Foreigner, Immigration